Pengaruh Pendekatan Realistic Mathematics Education Berbantuan Media Scratch untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SD - Violina Resty Lavayette; Siti Maryam Rohimah; Moh. Nurhadi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
Mathematics teaching at the elementary education level still faces challenges in improving students’ understanding of mathematical concepts, mainly because learning practices tend to be teacher-centered and have not optimally utilized interactive media. This study aims to analyze differences in the improvement of students’ mathematical concept understanding and evaluate the effectiveness of the Realistic Mathematics Education approach supported by Scratch media on elementary school students’ mathematical concept understanding. This study used a quantitative approach with a quasi-experimental nonequivalent groups design involving an experimental class and a control class. Data were collected through tests and observation, then analyzed using the N-Gain test, normality test, homogeneity test, independent samples t-test, and effect size calculation. The results show that the experimental class obtained an average N-Gain of 0.53 or 53.56%, while the control class obtained an average N-Gain of 0.32 or 32.41%. The hypothesis test results showed a significance value below 0.001, with Cohen’s d effect size of 1.005, which falls into the large effect category. These findings indicate that the Realistic Mathematics Education approach assisted by Scratch media is effective in improving elementary school students’ mathematical concept understanding. This study contributes to the development of mathematics learning strategies based on context and interactive media and provides practical implications for elementary school teachers in designing mathematics learning that is more relevant, engaging, and meaningful.